2021
DOI: 10.1186/s43045-021-00147-z
|View full text |Cite
|
Sign up to set email alerts
|

The ripple effect: a cross-sectional study on the repercussions of child maltreatment among Egyptian college students

Abstract: Background Child maltreatment is a global risk factor for mental health. The burden of child maltreatment is heaviest in low- and lower-middle-income countries, where most of the world’s children live. This study sheds light on the occurrence of child maltreatment within Egypt’s upper social class stratum, countering a long-held belief that violence against children only occurs within low-income households. In addition, the study examines the association between exposure to child maltreatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…We used multivariate analyses of variance (MANOVAs), repeated multivariate analyses of variance (rMANOVAs), and a hierarchical multiple regression to test the hypotheses. In an earlier publication (Fishere, 2021) we found that antipathy and sexual abuse predicted symptoms of PTSD, but neither physical abuse nor neglect. Accordingly, antipathy and sexual abuse were controlled for when looking at PTSD symptoms as an outcome variable, in addition to time since the stressful event (H3).…”
Section: Resultsmentioning
confidence: 67%
“…We used multivariate analyses of variance (MANOVAs), repeated multivariate analyses of variance (rMANOVAs), and a hierarchical multiple regression to test the hypotheses. In an earlier publication (Fishere, 2021) we found that antipathy and sexual abuse predicted symptoms of PTSD, but neither physical abuse nor neglect. Accordingly, antipathy and sexual abuse were controlled for when looking at PTSD symptoms as an outcome variable, in addition to time since the stressful event (H3).…”
Section: Resultsmentioning
confidence: 67%